The Polyvalent Nature of Proverbs in Akan Language: A Case of Ahwia Nsensanso in the Kwabere East District of Ashanti Region, Ghana (Global Journal of Human-Social Science, 2018)
The research looked at The Polyvalent Nature of Proverb A case of Ahwia Nsensanso in the Kwabere East District of Ashanti Region Ghana The purpose of the study was to use Ahwia Nsensanso as a case study to examine how the proverb is polyvalent in nature A qualitative approach was employed to assess and describe the related views concerning proverb use The study also adopted the traditional library research approach through the use of books articles journals and publications in as much as they contribute to the worth of the study It was informed by the Speech Act theory in linguistics and the philosophy of language The main findings of the study indicate that proverbs are of varied educational and socio cultural significance that enriches the culture and verbal esthetics of a society A remarkable observation was that when people speak their words do not have meaning in and of themselves Those speeches are very much affected by the situation the speaker and the listener This emphasizes that words alone do not have simple fixed meaning A conclusion drawn from the study is that as a conversational genre proverbs among the people of Ahwia Nsensanso Township are dynamic and self- renewing and this could apply to other areas of the Akan society
Keywords: proverbs; polyvalent; polyvalent nature of proverbs; speech act theory; linguistics; philosophy of language